Strengthening Student’s Spiritual Attitude Through Reflecting Learning Experiences by Teaching Materials Utilization - Nursobah, Asep; Suhartini, Andewi; Basri, Hasan; Hayati, Tuti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractSpiritual and social attitudes are important competencies that must be obtained by students through direct or indirect learning. Among the factors that determine the success of strengthening spiritual and social attitudes in learning are teaching materials that enable students to understand the experiences gained. The focus of this study is to strengthen students' spiritual and social attitudes through teaching materials that can make students give meaning to learning experiences. This research was conducted by observing and open questionnaire filling by students regarding the meaningfulness of teaching materials used in learning Islamic education (PAI) to strengthen the competency of spiritual attitudes and social attitudes of students. The results showed that the use of teaching materials in the student's book to reflect learning experiences and follow-up to improve their spiritual and social behaviour had fulfilled the need to reflect the values of spiritual and social attitudes from their learning experiences.AbstrakSikap spiritual dan sosial adalah kompetensi penting yang harus diperoleh oleh siswa melalui pembelajaran langsung atau tidak langsung. Di antara faktor-faktor yang menentukan keberhasilan penguatan sikap spiritual dan sosial dalam belajar adalah bahan ajar yang memungkinkan siswa untuk memahami pengalaman yang diperoleh. Fokus penelitian ini adalah memperkuat sikap spiritual dan sosial siswa melalui bahan ajar yang dapat membuat siswa memberi makna pada pengalaman belajar. Penelitian ini dilakukan dengan mengobservasi dan pengisian quesioner oleh siswa mengenai kebermaknaan bahan ajar yang digunakan dalam belajar PAI untuk menguatkan kompetensi sikap spiritual dan sikap sosial siswa. Hasil penelitian menunjukkan bahwa pemanfaatan bahan ajar yang ada pada buku siswa untuk memaknai pengalaman belajar dan tindak lanjut bagi perbaikan perilaku spiritual dan sosial mereka, belum memenuhi kebutuhan refleksi nilai-nilai sikap spiritual dan sosial dari pengalaman belajar mereka. How to Cite: Nursobah, A., Suhartini, A., Basri, H., Hayat, T. (2019). Strengthening Student’s Spiritual Attitude Through Reflecting Learning Experiences by Teaching Materials Utilization. TARBIYA: Journal of Education in Muslim Society, 6(2), 117-133. doi:10.15408/tjems.v6i2. 11915.